Assessing Structural Safety of an Arch Dam Using in Situ Vibration Tests. Issue 2 (November 2021) - Gaftoi, Daniel; Abdulamit, Altan; Aldea, Alexandru; Sarghiuta, Radu; Popescu, Catalin
Abstract: Safety of large dams has always been a major concern for engineers throughout the world but also for public opinion, mass-media and politicians. This is usually based on the fact that the collapse of a large dam could result in huge consequences such as fatalities, economic and/or environmental losses. Nowadays, it is well known that an important factor adversely influencing the safety of such a complex structure like a dam is represented by ageing as a process and ageing related phenomena. Since some 85% of all existing large dams are built in the last 50 years, safety influenced by different decay processes became an important issue to be analysed by dam engineers. In this regard, in situ ambient vibration measurements used to identify the dynamic response characteristics of a large dam seems to represent an appealing non-destructive technique to assess the structural and material characteristics changes and thus to monitor the safety status of the structure. The paper presents the use of the above mentioned procedure by a Romanian team of dam specialists who developed a method combining experimental and analytical techniques for the assessment of the health status of large concrete dams. The Global Elastic Modulus Method (GEMM) was initially used for analysing buttress dams, then it was extended to assess arch dams' safety state. The most recent evaluation was made upon a 48 m height arch dam in Romania, Cincis dam, located in the central part of the country. The paper is structured into 3 main parts: Introduction, explaining the concept of the hybrid model (the mathematical model bounded to a certain in situ measurement program and calibrated using the recorded data) and of the global elastic modulus (GEM) associated with the dam structure; Experimental, presenting the used equipment, measuring scheme and the processing of the recorded data, ending with the results from spectral analyses; Analytical, presenting the mathematical model developed for the dam structure and its calibration aiming to identify the natural response frequencies and the corresponding mode shapes of the analysed structure. Final conclusions and recommendations are made.